2013
DOI: 10.3109/1547691x.2013.843620
|View full text |Cite
|
Sign up to set email alerts
|

Immune stimulation following dermal exposure to unsintered indium tin oxide

Abstract: In recent years, several types of pulmonary pathology, including alveolar proteinosis, fibrosis, and emphysema, have been reported in workers in the indium industry. To date, there remains no clear understanding of the underlying mechanism(s). Pulmonary toxicity studies in rats and mice have demonstrated the development of mediastinal lymph node hyperplasia and granulomas of mediastinal lymph nodes and bronchus-associated lymphoid tissues following exposure to indium tin oxide. Given the association between ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…In the workplace, reduced integrity or a barrier dysfunction of the skin can lead to increased dermal absorption of chemicals allowing for the entrance of larger molecules (Anderson and Meade, 2014). There is some evidence on the ability of UITO to stimulate an immune response in mice upon dermal exposure (Brock et al, 2014). In addition, Tinkle et al have shown that particles as large as 1 μm in size can penetrate the intact epidermis (Tinkle et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the workplace, reduced integrity or a barrier dysfunction of the skin can lead to increased dermal absorption of chemicals allowing for the entrance of larger molecules (Anderson and Meade, 2014). There is some evidence on the ability of UITO to stimulate an immune response in mice upon dermal exposure (Brock et al, 2014). In addition, Tinkle et al have shown that particles as large as 1 μm in size can penetrate the intact epidermis (Tinkle et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Solubilazion by macrophages in vitro of ITO compounds via the phagolysomal acidification pathway, resulting in cell death and release of indium ions has also been shown (Gwinn et al, 2013). Though much work has been done in recent years studying the effects of ITO toxicity (Lison et al, 2009; Badding et al, 2015, 2016,2014; Brock et al, 2014), the amount of conflicting data in relation to UITO- and SITO-mediated responses makes it apparent that the pathogenesis of ITO-mediated disease warrants further research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Penetration through the breached skin was also demonstrated. Phenotypic analysis of draining lymph node cells following intradermal injection with 5% UITO yielded a profile consistent with a T-cell-mediated response (Brock et al, 2014).…”
Section: Sensitizationmentioning
confidence: 98%
“…Exposure produced no changes in body weight, no systemic signs of toxicity or visual signs of inflammation at the exposure sites (Brock et al, 2014).…”
Section: Local Effects On Skin and Mucous Membranesmentioning
confidence: 99%